Highly sensitive in vitro bioassay for luteinizing hormone and chorionic gonadotropin allowing their measurement in plasma - Danièle Klett; Yves Combarnous (Bioscientifica, 2021)
In previous studies, we had shown the synergistic effect of 10−5 M forskolin (FSK) on the detection threshold of the cyclic AMP response to luteinizing hormones (LH) and chorionic gonadotropins (CG) from various species in the mouse Leydig tumor cell (mLTC) cell line. Independently, we started to study the effect of 10−12-10−6 M oxytocin (OXT) also on the cyclic AMP response to LH and CG preparations on these same cells and found an amplifying effect on the luminescence response caused by gonadotropins. The aim was then to explore the effects of 10−12-10−6 M OXT on the gonadotropin-induced cAMP response, in the presence or absence of 10 μM FSK to optimize the assay down to a sensitivity compatible with the detection of the circulating concentrations of these hormones in various species. Finally, the optimization relies on three independent phenomena: (1) the inhibition of nucleotide phosphodiesterase by IBMX (3-isobutyl-1-methylxanthine) to avoid cAMP degradation; (2) the strong synergy of 10 μM forskolin with low concentrations of LH or CG during the 1-h luminescence measurement; (3) the stimulatory effect of 10−8M OXT on the amplitude of transfected cAMP-sensitive luciferase response. By doing this, the detectable concentrations are at the 1-10 pg/well (pM range) for the LHs and CGs from various species. The bioactivities of circulating LHs and CGs in blood or urine are therefore expected to be measurable in 10 μL-plasma samples from mammalian species and maybe others. Indeed, a preliminary study with equine and donkey plasma samples shows that the measured bioactivity was fully inhibited by a specific MAB against the receptor-binding region of equine LH (eLH) and equine CG (eCG), thus eliminating a possible response due to interfering substances other than eLH or eCG. From these data, it is expected that the bioactivity profiles of these hormones will be measurable in the blood of human, equine, and ovine species and very likely in rodents, ruminants, and hopefully in most other mammalian species.